1998
DOI: 10.1136/hrt.80.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II modulates cardiovascular autonomic control in the absence of baroreflex loading

Abstract: Objective-To investigate the eVects of angiotensin II in the absence of baroreflex activation. Design-Ten healthy male volunteers were studied in a single blind, randomised, crossover study of heart rate variability during intravenous angiotensin II infusion (5-20 ng/kg/min) compared with a control pressor infusion of phenylephrine (0.7-2.8 µg/kg/min). Each infusion was titrated to increase mean blood pressure by 20 mm Hg; sodium nitroprusside was then infused simultaneously to restore blood pressure to baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(34 reference statements)
0
16
0
1
Order By: Relevance
“…Central and peripheral actions resulting in inhibition of cardiac parasympathetic control and facilitation of sympathetic activity have been demonstrated in animals [6][7][8]. In humans, our studies have shown that cardiac vagal control is reduced by angiotensin II [3], and a facilitatory action on the baroreflex control of sympathetic activity has also been described [27]. These actions appear to be mediated by AT " receptors [28], and therefore pharmacological blockade might be expected to increase measures of cardiac vagal activity and reduce those related to sympathetic activity.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Central and peripheral actions resulting in inhibition of cardiac parasympathetic control and facilitation of sympathetic activity have been demonstrated in animals [6][7][8]. In humans, our studies have shown that cardiac vagal control is reduced by angiotensin II [3], and a facilitatory action on the baroreflex control of sympathetic activity has also been described [27]. These actions appear to be mediated by AT " receptors [28], and therefore pharmacological blockade might be expected to increase measures of cardiac vagal activity and reduce those related to sympathetic activity.…”
Section: Discussionmentioning
confidence: 65%
“…These effects may be mediated both centrally and peripherally. In healthy human volunteers, we have shown previously that exogenous angiotensin II reduces the cardiac vagal modulation of heart rate [3]. Conversely, we and others have shown that, in patients with heart failure, indices of cardiac vagal activity are increased by ACE inhibitors [9][10][11][12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The following time domain measures of heart rate variability were determined : SDNN (standard deviation of R-R interval values), RMSSD (root-mean-square of successive R-R interval differences) and pNN50 (percentage of successive R-R interval differences exceeding 50 ms). In addition, we determined the interquartile differences (75th-25th percentile) of the frequency distributions of the total number of R-R intervals (IQDNN) and of successive R-R interval differences (IQDSD) [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…s Key words Polymorphism · renin-angiotensin system · heart rate variability of AII infusion on high frequency measures of HRV mediated by the vagus [4]. Plasma A II concentration is dependent not only upon the stimulus of renin production but on the activity of angiotensin-converting enzyme (ACE).…”
Section: Introductionmentioning
confidence: 99%